2014
DOI: 10.1177/030089161410000201
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Free DNA in a Screening Program for Early Colorectal Cancer Detection

Abstract: The use of cfDNA quantification to predict adenocarcinoma at an early stage in high-risk (aged >50 years and FOBT positive) subjects seems to be promising but needs more sensitive methods to improve cfDNA detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 32 publications
1
46
0
1
Order By: Relevance
“…EGFR mutations have also been shown to be of prognostic and predictive value, and patients with an activating mutation in EGFR in cfDNA have been reported to respond significantly better to TKIs (27). KRAS gene alterations detected in cfDNA have also been used as prognostic biomarkers, mainly in colorectal and pancreatic cancer (28,29). However, their predictive and prognostic value in NSCLC remains undefined, and to an extent controversial, due to the relatively few studies performed.…”
Section: Circulating Free Dna (Cfdna) As Prognostic and Monitoring Tementioning
confidence: 99%
“…EGFR mutations have also been shown to be of prognostic and predictive value, and patients with an activating mutation in EGFR in cfDNA have been reported to respond significantly better to TKIs (27). KRAS gene alterations detected in cfDNA have also been used as prognostic biomarkers, mainly in colorectal and pancreatic cancer (28,29). However, their predictive and prognostic value in NSCLC remains undefined, and to an extent controversial, due to the relatively few studies performed.…”
Section: Circulating Free Dna (Cfdna) As Prognostic and Monitoring Tementioning
confidence: 99%
“…Similarly, some studies have found very low mutation rate in cfDNA compared to tissues. KRAS mutations in plasma was 3% compared with 45% rate observed in the matched tissues from colorectal adenocarcinoma and colorectal high-grade intraepithelial neoplasia [61].…”
Section: Limitationsmentioning
confidence: 86%
“…In this technique a mismatched primer is used for PCR, which introduces restriction site and can be used to differentiate the wild type allele from mutant allele. The technique has been tested in differentiating early colorectal lesions based on the presence of mutant KRAS status in cfDNA and was found to have significant predictive capability [60][61][62].…”
Section: Methods Targeting Druggable Mutation and Other Aberrations Imentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14] Liquid biopsy of circulating CRC cells and cell free DNA from plasma are experimental modalities likely to become clinical reality in the near future. 15 All these tests ultimately help to screen and triage high-risk patients who can be further motivated to undergo colonoscopy ( Table 4). The ultimate success of any CRC screening program is heavily dependent on the participation and compliance of the people being screened, 16 as well as the quality of the colonoscopy and polypectomy in the community.…”
Section: Tropical Gastroenterology 2014;35(1):1-4mentioning
confidence: 99%